Virginia Woolf's Critique of Philosophy and Development of Aesthetic Prose. - Bushnell, Emma Lia. (Tufts Archival Research Center, 2005)
In this thesis I first examine Virginia Woolf's rejection of philosophy that begins in "Mrs. Dalloway" and matures in "To the Lighthouse." I then investigate her development of a prose style that encompasses aspects of both poetry and visual art, and how she offers this aesthetic prose style as an alternate form of representation that is more useful than philosophy is.